2011
DOI: 10.1097/aln.0b013e318231fc11
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Consequence of the A118G μ Opioid Receptor Polymorphism on Morphine- and Fentanyl-mediated Modulation of Ca2+Channels in Humanized Mouse Sensory Neurons

Abstract: Background The most common functional single nucleotide polymorphism of the human OPRM1 gene, A118G, has been shown to be associated with inter-individual differences in opioid analgesic requirements, particularly with morphine, in patients with acute postoperative pain. The purpose of the present study was to examine whether this polymorphism would modulate the morphine and fentanyl pharmacological profile of sensory neurons isolated from a humanized mouse model homozygous for either the 118A or 118G allele. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 35 publications
4
48
0
1
Order By: Relevance
“…Naive h/mOPRM1-118AA and 118GG mice are equally sensitive to fentanyl, supporting previous findings using this model (Mahmoud et al, 2011). As a highly potent, efficacious, and brain-penetrant agonist, fentanyl has a large receptor reserve in vivo that appears to override differences in tissue receptor content.…”
Section: Discussionsupporting
confidence: 79%
“…Naive h/mOPRM1-118AA and 118GG mice are equally sensitive to fentanyl, supporting previous findings using this model (Mahmoud et al, 2011). As a highly potent, efficacious, and brain-penetrant agonist, fentanyl has a large receptor reserve in vivo that appears to override differences in tissue receptor content.…”
Section: Discussionsupporting
confidence: 79%
“…Also, some reports have evidenced that the polymorphisms could affect the protein's functionality such as its interaction with ligands, the dimerization, or signalling. As for LEPR, fluctuations of the alpha carbons support the hypothesis that the change of a single amino acid could modify the LEP-LEPR interaction or LEPR function (Basu et al, 2011;Mahmoud et al, 2011;Marie et al, 2012;Yates and Sternberg, 2013).…”
Section: Discussionmentioning
confidence: 66%
“…However, one study has reported the opposite result in humanized mice expressing human MOR-N or MOR-D. This study found that Ca V currents from trigeminal ganglion neurons are inhibited at lower morphine doses when the neurons are injected with human MOR-D mRNA as compared with the inhibition observed in neurons injected with MOR-N mRNA [11]. The discrepancy between this report and the previously mentioned studies could be due to the fact that trigeminal ganglia have several Ca V types contributing to the voltage gated calcium currents [28,29] while Lopez Soto et al [8] analyzed Ca V 2.2 transfected in HEK293 cells and Margas et al [7] studied SGC neurons where the Ca V 2.2 are the predominant voltage gated channels.…”
Section: A118g Modifies Mor Activitymentioning
confidence: 61%
“…At molecular level, we and others have reported differences in the agonist affinity and potency, intracellular cascades and effectors involved in MOR effects [4][5][6][7][8][9][10][11]. On the other hand, clinical studies have demonstrated changes in pain sensation and morphine requirements under different pain conditions [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%